Analisis Aplikasi Konsep Gaya dalam Fisika yang Berkaitan dengan Bidang Biologi - Toto Toto; Lia Yulisma (Universitas Negeri Jakarta, 2017)
Abstract In general, students of Biology faculty study program of Universitas Galuh Ciamis viewed physics as a difficult subject (based on interview result of writer with some students). This statement is reinforced by the acquisition of less satisfactory physics courses. They are less interested in the subject of physics with a variety of reasons including counting material that requires them to memorize many formulas and theories. In the course of physics in the biology program should be equipped application of concepts and principles of physics in the field of biology. It is very important to facilitate students in mastering and enjoying physics courses. In this study, documentation study of biology books in the subjects of General Biology in 1st semester. Based on the analysis there are application of the concept of style in the subject material of General Biology namely: capillarity style on xylem and phloem; Force on muscle tissue; And food peristaltic style. The results of this study are useful as a basis for the preparation of physics-oriented teaching materials of biological science, so that biology students are expected to be interested in physics. As a recommendation that analysis of the application of concepts and principles of physics in biology must be done in a continuous manner. Keywords: Style concept application. Abstrak Pada umumnya  mahasiswa prodi pendidikan biologi FKIP Universitas Galuh Ciamis  memandang fisika sebagai mata kuliah yang sulit (berdasarkan hasil wawancara penulis dengan beberapa mahasiswa). Pernyataan ini diperkuat  dengan perolehan nilai mata kuliah fisika yang kurang memuaskan. Mereka kurang tertarik pada mata kuliah fisika dengan berbagai alasan diantaranya banyak materi hitungan yang mengharuskan mereka menghapal banyak rumus dan teori. Dalam perkuliahan fisika pada prodi biologi seharusnya dilengkapi aplikasi konsep dan prinsip-prinsip fisika dalam bidang biologi. Hal tersebut sangat penting untuk mempermudah mahasiswa dalam menguasai dan menyukai mata kuliah fisika. Dalam penelitian ini dilakukan studi dokumentasi terhadap buku biologi pada mata kuliah Biologi Umum pada semester 1. Berdasarkan analisis terdapat aplikasi konsep gaya dalam materi mata kuliah Biologi Umum yaitu : gaya kapilaritas pada xilem dan floem; gaya pada jaringan otot; dan gaya peristaltik makanan. Hasil studi ini bermanfaat sebagai dasar pijakan dalam penyusunan bahan ajar fisika yang berorientasi ilmu hayati, sehingga mahasiswa biologi diharapkan tertarik terhadap fisika. Sebagai rekomendasi bahwa analisis aplikasi konsep dan prinsip fisika dalam biologi mesti dilakukan secara berkesimbungan. Kata kunci: Aplikasi konsep gaya.